2013
DOI: 10.1080/14635240.2012.750070
|View full text |Cite
|
Sign up to set email alerts
|

Missed opportunities for early HIV diagnosis: critical insights from the stories of Kenyan women living with HIV

Abstract: Early HIV testing is critical to prevention and timely treatment. Missed opportunities for HIV diagnosis can result in unnecessary deaths at a time when access to antiretroviral treatment proves life saving. While HIV prevention and treatment research has increased, less research exists on women's experiences with HIV diagnosis, despite the fact that women are most affected. Insights from local women are critical in designing culturally meaningful interventions that thwart missed opportunities for early HIV di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…About a quarter of included studies (n=15) described sociocultural norms, such as traditional beliefs, gender roles and gender norms, as key factors influencing pregnant women’s acceptability of HIV/syphilis RDT at ANCs 35 36 39 41 51 57 63 69 70 75 80 92–96. Five studies reported that traditional beliefs regarding pregnancy can prevent women from seeking care at ANCs 35 39 57 63 92.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…About a quarter of included studies (n=15) described sociocultural norms, such as traditional beliefs, gender roles and gender norms, as key factors influencing pregnant women’s acceptability of HIV/syphilis RDT at ANCs 35 36 39 41 51 57 63 69 70 75 80 92–96. Five studies reported that traditional beliefs regarding pregnancy can prevent women from seeking care at ANCs 35 39 57 63 92.…”
Section: Resultsmentioning
confidence: 99%
“…A case study from Indonesia reported healthcare workers had denied the request from pregnant women of HIV testing if their husbands refused to give permission 46. Intentional and unintentional breaches of pregnant women confidentiality to their husband or family members were also more likely to occur in these settings 41 46 93 96. We found six studies that included male partners in the study design in an effort to enhance women’s acceptability of testing 69 70 75 80 94 95.…”
Section: Resultsmentioning
confidence: 99%
“…Early diagnosis and start of medical treatment might have greatly contributed to participant’s survival. Many studies have reported missed diagnoses that have resulted in a number of deaths that could have been prevented with antiretroviral treatment [ 49 , 50 ]. However, we do not know if P’s husband already knew that he was HIV positive and used P’s aunt (a nurse) as a means to get P tested without questioning the rationale for HIV testing in a monogamous marriage that supposedly excludes third party relationship.…”
Section: Discussionmentioning
confidence: 99%
“…This US phenomenon of missed opportunities in HIV testing reflects a common global theme: works have described missed opportunities in Ethiopia, France, Ireland, Kenya, and Scotland in recent years. 2631 Deblonde reports an estimated 30% of people living with HIV in the European Union and neighbouring countries are unaware of their infection and suggests missed opportunities for diagnosis due to a variety of factors including patient perceptions, legal or financial factors, and attitudes and practices of health care providers. 32 HIV testing guidelines have been introduced in Scotland and the United Kingdom; similarly to the US, both countries have had challenges in applying these guidelines in practice.…”
Section: Discussionmentioning
confidence: 99%